(3GdcTGa Yf MbGFb GdJfRjd hYjhf GdCbGhjd aj hLhg GdJChjds - (3GdnqRnerNnTpQj GdNhGQRej, CHh GdbGSe, LGQ Gddg, eMehO Hf YeQ Hf eMeO Hf CMeO, (B538 (3g`s ((3ESeGYjd Hf eMeO Hf CHj GdaJM GdOfhTQjs)
(3ChdgG (B:s
(3HYO GdHSedI ; dMeO ddg GdPj GfRd GdbQBf cdGeG eDdaG efXeG Ke Ef CedC GdYdhe HeG jZeQ GdbQGFM Yde GdJaSjQ GdPj dG jJe dJYGWjg Cf Cedj Ydjge aj GdcTa Yf MbGFb GdJfRjds
(3BNQgG (B:s
(3dbO fRdJ Ydqi ShQJGf eG CfRd eKdgeG, hEfc df JbQC ShQJjf CMH hdG CQVi YfO Gddg efgeG hjbGd ddeYhPJjf(B: (3GdebTbTJGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 178s
(3eYLe GdeDdajf (B3 / 822s
(3cTa GdXfhf (B2 / 1475s
(3TPQGJ GdPgH (B4 / 118s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs